Social Change and the Culture as the Basic of Wulandoni-Pantai Harapan Reconciliation - Blajan Konradus; Agustinus Gergorius Raja Dasion (International Journal of Social Science and Religion (IJSSR), 2021)
This study aims to explain social change of post-conflict of the Wulandoni - Pantai Harapan community and what kind of cultural communication space should be built for sustainable reconciliation and peace. The two focus studies above have become very central in reading and analysing the reality of the conflict between the two villages. By using ethnographic method, this study found three things. First, the conflict between Wulandoni and Pantai Harapan villages is not a religious conflict. Even so, it cannot be denied that the discourse on religious conflict was quite developed at that time because the cultural and religious realities of the two villages were quite different. Second, the Wulandoni-Pantai Harapan conflict caused social change and the loss of kinship between the people, especially the loss of the Wulandoni barter market. Third, post-conflict reconciliation and peace efforts are immediately carried out thanks to the cultural and economic relations between the people on the south coast of Lembata Island. These social, economic and cultural kinship relationships are important pillars in creating peace and harmony between communities. This study also opens the discourse of reconciliation and peace based on local culture and economy in the south of Lembata Island.